2020
DOI: 10.1016/j.celrep.2020.107864
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Mechanisms of Over-Representation of Landmarks and Rewards in the Hippocampus

Abstract: Highlights d CA1 over-representation of reward and landmark emerge with distinct time courses d These cells form stable singularities during experiencedependent map consolidation d The over-representation of landmark but not reward is dependent on Shank2

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
87
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 61 publications
(95 citation statements)
references
References 58 publications
8
87
0
Order By: Relevance
“…Although both the bottleneck model and the over-representation model exhibited chunking effects, the over-representation model is particularly consistent with the experimental observation because theta sequences are segmented at salient landmarks and rewards 32 which are over-represented by hippocampal place cells 38,39 . These results demonstrates that LAM provides a unified mechanism for graph-based representations 6,7 and chunking of sequential activities 32 .…”
Section: Chunked Sequential Activities In Asymmetric Lamsupporting
confidence: 76%
See 1 more Smart Citation
“…Although both the bottleneck model and the over-representation model exhibited chunking effects, the over-representation model is particularly consistent with the experimental observation because theta sequences are segmented at salient landmarks and rewards 32 which are over-represented by hippocampal place cells 38,39 . These results demonstrates that LAM provides a unified mechanism for graph-based representations 6,7 and chunking of sequential activities 32 .…”
Section: Chunked Sequential Activities In Asymmetric Lamsupporting
confidence: 76%
“…We found that both local bottlenecks and over-representations induce the chunking of sequential activities in asymmetric LAM. The over-representation model is particularly interesting because it accounts for the role of salient landmarks and rewards which are overrepresented by place cells 38,39 . We may be able to apply a ring-shape structure with two overrepresentations for modeling typical experiments in which animals run back and forth on a 1-D track to get rewards at both ends, considering that many place cells are directionselective in such experimental setting 47 .…”
Section: Discussionmentioning
confidence: 99%
“…By conducting a cell‐by‐cell comparison of maps imaged in adjacent sessions, we found that hippocampal map stability is tightly regulated in a salience‐dependent, location‐specific manner (Figure 2). Before reward rearrangement, place‐field stability of the reward location and the landmark location was significantly higher than that of non‐salient locations (Figure 2a,d; Sato et al, 2020). Reward rearrangement triggered a significant reduction in place‐field stability of the previous reward location and non‐salient locations in early phase re‐training (Figure 2b,d).…”
Section: Main Bodymentioning
confidence: 92%
“…It is well‐established that locations associated with behaviorally relevant salient features, such as reward, safety, and local cues, are over‐represented by a disproportionately large number of place cells (PCs) in the hippocampus (Bourboulou et al, 2019; Dupret, O'Neill, Pleydell‐Bouverie, & Csicsvari, 2010; Gauthier & Tank, 2018; Hetherington & Shapiro, 1997; Hollup, Molden, Donnett, Moser, & Moser, 2001; O'Keefe & Conway, 1978; Sato et al, 2020; Wiener, Paul, & Eichenbaum, 1989; Zaremba et al, 2017). Recently, we demonstrated that de novo establishment of these disproportionate maps involves the selective stabilization of PCs that encode salient locations following their conversion from non‐PCs (Sato et al, 2020). However, the cellular dynamics underlying the plasticity of pre‐established maps remained unknown.…”
Section: Main Bodymentioning
confidence: 99%
See 1 more Smart Citation